Szolgáltatásminőség a menedzsment tanácsadásban = Service quality in management consulting - Schmuck, Roland (Közép-Európai Közlemények, 2018)
Defining quality in case of organizations in the service sector is not evident because there is no standardized way of measuring service quality that could be comparable with each other like in the case of psychical products. It is even harder to judge the quality of services with unknown results beforehand. Management consulting is such a service.1 Management consultants provide solutions to the problems of organizations. There is no one best way to manage quality in this case. The main goal is to clarify which quality management methods can work in such circumstances. Service quality is very important when getting new contracts.2 Management consulting is mainly based on trust as the outcome of the consulting service is not immediate and hard to measure.3 Consulting companies should not only keep the technical standards but have to satisfy the customers’ requirements to provide a quality service.3 The research is mainly based on literature research and the own experiences of the author as an ISO 9001 quality management auditor. This gives the paper a quality management view, but other aspects are considered as well. Management consultants have to build trust.4 A good idea to achieve this is to concentrate on quality. Consulting companies can choose from several methods to increase the quality of their services. In most cases these are soft methods because of the lack of statistical data. In this paper the most commonly used methods are shown. Many of the consulting firms operate ISO 9001 standard-based quality management systems or TQM in their own organizations. Back in time this was a different story. In the 1980s consulting firms rather worked on their clients’ quality concerns not on their own. This has change a lot since that. Nowadays there is so high need of quality operation with reduced costs that the consulting firms themselves also operate quality management systems. These systems can reduce costs as well by making better decisions and decreasing the cost of bad quality such as faulty products and guarantee costs.5 The basic ideas of the ISO 9001 applied to the consulting industry is shown in this paper.